Alex Cross's trial - Patterson, James and Dilallo, Richard (London Arrow Books, 2010)
As a lawyer in early-twentieth-century Washington DC, Ben Corbett represents the toughest cases. Fighting against oppression and racism, he risks his family and his life in the process. When President Theodore Roosevelt asks Ben to return to his hometown to investigate rumours of the resurgence of the Ku Klux Klan there, he cannot refuse.
Keywords: Race relations -- Southern States -- Racism